Experimental and Theoretical Evaluation of Ultrasonic Velocities of Binary Liquid Mixtures of Anisaldehyde and Toluene at Different Temperatures - CH. Srinivasu; K. Narendra; CH. Kalpana (E-Journal of Chemistry)
Theoretical velocities of binary liquid mixtures of anisaldehyde with toluene at 303.15, 308.15, 313.15 and 318.15 K have been evaluated by using theoretical models of liquid mixtures such as Nomoto, Van Dael-Vangeel, Schaff’s collision factor theory and Junjie’s relations. Density and ultrasonic velocity of these mixtures have also been measured as a function of concentration and temperature and the experimental values are compared with the theoretical values. A good agreement has been found between experimental and Nomoto’s theoretical ultrasonic velocities. The results are explained in terms of intermolecular interactions occurring in these binary liquid mixtures.